Neogene and Quaternary radiolarians from the Izu-Bonin Forearc in the western Pacific Ocean - Yu-Jing Wang; Qun Yang (PANGAEA, 1992)
Radiolarians were recovered from three of the five holes investigated during Leg 125. Relative abundances are estimated at Holes 782A and 784A, where preservation is poor to good. Rare, poorly preserved radiolarians are present in Hole 786A. Seven radiolarian zones are recognized in the latest early- middle Miocene to early Pleistocene of Holes 782A and 784A. These zones are approximately correlated to the zones of Sanfilippo and others published in 1985.
Supplement to: Wang, Y-J; Yang, Q (1992): Neogene and Quaternary radiolarians from Leg 125. In: Fryer, P; Pearce, JA; Stokking, LB; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 125, 95-112, https://doi.org/10.2973/odp.proc.sr.125.174.1992